2006
DOI: 10.1038/oby.2006.13
|View full text |Cite
|
Sign up to set email alerts
|

Do Energy Density and Dietary Fiber Influence Subsequent 5‐Year Weight Changes in Adult Men and Women?

Abstract: Results:Mean 5-year changes in body weight (BW) were 1.2 Ϯ 3.9 and 1.3 Ϯ 4.6 kg for men and women, respectively. In general, neither ED nor any of the dietary components was associated with subsequent change in BW. In women, ED was positively associated with weight gain among the obese (BMI Ͼ 30 kg/m 2 ) and inversely associated with weight gain in normal-weight women (BMI Ͻ 25 kg/m 2 ) (p ϭ 0.01). However, in men there was a nonsignificant inverse trend between ED and weight gain in the obese and no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 20 publications
2
69
1
Order By: Relevance
“…Besides total energy intake, dietary energy density (kcal/g) defined as the amount of energy in a given weight of food has received considerable attention in recent years as one of the main determinants of alarming obesity trends (WHO/FAO, 2003). Although some studies have failed to find any significant association between consumption of energy-dense diets and obesity (De Castro, 2004;Iqbal et al, 2006;Du et al, 2009), others have reported a significant positive association (Howarth et al, 2006;Ledikwe et al, 2006aLedikwe et al, , 2007Mendoza et al, 2007;Bes-Rastrollo et al, 2008;Savage et al, 2008). Such significant findings have also been confirmed by clinical trials, where reduction in dietary energy density has been resulted in significant weight loss (Ello-Martin et al, 2007).…”
Section: Introductionsupporting
confidence: 60%
“…Besides total energy intake, dietary energy density (kcal/g) defined as the amount of energy in a given weight of food has received considerable attention in recent years as one of the main determinants of alarming obesity trends (WHO/FAO, 2003). Although some studies have failed to find any significant association between consumption of energy-dense diets and obesity (De Castro, 2004;Iqbal et al, 2006;Du et al, 2009), others have reported a significant positive association (Howarth et al, 2006;Ledikwe et al, 2006aLedikwe et al, , 2007Mendoza et al, 2007;Bes-Rastrollo et al, 2008;Savage et al, 2008). Such significant findings have also been confirmed by clinical trials, where reduction in dietary energy density has been resulted in significant weight loss (Ello-Martin et al, 2007).…”
Section: Introductionsupporting
confidence: 60%
“…To date, there has been only one longitudinal analysis of the relationship between energy density and subsequent weight gain in a free-living population, which found no evidence to support an effect in the general adult population. 19 However, any effect of DED on weight gain may have been diluted because DED was calculated including drinks and the analysis did not consider the impact of misreporting of EI. Abbreviations: BMI, body mass index; CI, confidence interval; DED, dietary energy density.…”
Section: Discussionmentioning
confidence: 99%
“…18 In addition, the only longitudinal analysis of DED and subsequent weight change over 5 years in adults showed no evidence of an association in the general population. 19 To date, there has been no prospective analysis of the effect of energy-dense diets on subsequent fatness or weight status in a population of free-living children. The aim of this study is to test the hypothesis that high DED at age 5 and 7 years is associated with increased fat mass or excess adiposity among 9-year-old children in the Avon Longitudinal Study of Parents and Children (ALSPAC).…”
Section: Introductionmentioning
confidence: 99%
“…Results from crosssectional studies of energy density of the diet and adiposity have been inconsistent (Drewnowski et al, 2004) and prospective observational data are sparse. The association between energy density and weight change was examined in a cohort of middle-aged Danish men and women (Iqbal et al, 2006). In the overall cohort, energy density at baseline was not substantially associated with 5-year weight gain.…”
Section: S77mentioning
confidence: 99%